Effects of prior hamstring strain injury on strength, flexibility, and running mechanics - Silder, A.; Thelen, D. G.; Heiderscheit, B. C. (Clinical Biomechanics, 2010)
Previous studies have shown evidence of residual scar tissue at the musculotendon junction following a hamstring strain injury, which could influence re-injury risk. The purpose of this study was to investigate whether bilateral differences in strength, neuromuscular patterns, and musculotendon kinematics during sprinting are present in individuals with a history of unilateral hamstring injury, and whether such differences are linked to the presence of scar tissue.